Soundscape descriptors in eighteen languages: translation and validation through listening experiments - Aletta, Francesco; Mitchell, Andrew; Oberman, Tin; Kang, Jian; Khelil, Sara; Bouzir, Tallal Abdel Karim; Berkouk, Djihed; Xie, Hui; Zhang, Yuan; Zhang, Ruining; Yang, Xinhao; Li, Min; et al. (Elsevier Ltd, 2024)
This paper presents the outcomes of the “Soundscape Attributes Translation Project” (SATP), an international initiative addressing the critical research gap in soundscape descriptors translations for cross-cultural studies. Focusing on eighteen languages – namely: Arabic, Chinese, Croatian, Dutch, English, French, German, Greek, Indonesian, Italian, Japanese, Korean, Malay, Portuguese, Spanish, Swedish, Turkish, and Vietnamese – the study employs a four-step procedure to evaluate the reliability and cross-cultural validity of translated soundscape descriptors. The study introduces a three-tier confidence level system (Low, Medium, High) based on “adjusted angles”, which are a measure proposed to correct the soundscape circumplex model (i.e., the pleasant-eventful space proposed in the ISO 12913 series) of a given language. Results reveal that most languages successfully maintain the quasi-circumplex structure of the original soundscape model, ensuring robust cross-cultural validity. English, Arabic, Chinese (Mandarin), Croatian, Dutch, German, Greek, Indonesian, Italian, Spanish, Swedish, and Turkish achieve a “High” confidence level. French, Japanese, Korean, Malay, Portuguese, and Vietnamese demonstrate varying confidence levels, highlighting the importance of the preliminary translation. This research significantly contributes to standardized cross-cultural methodologies in soundscape perception research, emphasizing the pivotal role of adjusted angles within the soundscape circumplex model in ensuring the accuracy of dimensions (i.e., attributes) locations. The SATP initiative offers insights into the complex interplay of language and meaning in the perception of environmental sounds, opening avenues for further cross-cultural soundscape research.